Vascular reconstruction of the decellularized biomatrix for whole-organ engineering—a critical perspective and future strategies - Gupta, Santosh; Sharma, Akriti; Petrovski, Goran; Verma, Rama Shanker (Frontiers in Bioengineering and Biotechnology, 2023)
Whole organ re-engineering is the most challenging goal yet to be achieved in tissue engineering and regenerative medicine. One essential factor in any transplantable and functional tissue engineering is fabricating a perfusable vascular network with macro and micro-sized blood vessels. Whole organ development is more practical using decellularized organ biomatrix (DOB) as it provides a native biochemical and structural framework of a particular organ. However, reconstructing vasculature and re-endothelization in DOB is a highly challenging task and has not been achieved for constructing a clinically transplantable vascularized organ with an efficient perfusable capability. Here in this review article, we have critically and articulately emphasized factors that have been studied for the vascular reconstruction in the DOB. Further, we have highlighted the factors used for vasculature development studies in general and how they can be used for whole organ vascular reconstruction. We have also analyzed in detail the strategies that have been explored so far for vascular reconstruction and angiogenesis in DOB for functional and perfusable vasculature development. Finally, we have discussed some of the crucial factors that have been largely ignored in the vascular reconstruction of DOB and the future directions that should be addressed systematically.